Plastic burial by flash-flood deposits in a prodelta environment (Gulf of Patti, Southern Tyrrhenian Sea). (August 2022) - Pierdomenico, Martina; Ridente, Domenico; Casalbore, Daniele; Di Bella, Letizia; Milli, Salvatore; Chiocci, Francesco Latino
Abstract: Plastic pollution affects all oceans and sequestration of plastics in sediments is considered its ultimate sink. We report evidence of macroplastic burial retrieved within a sediment core collected at 38 m depth at the mouth of the Mazzarrà River, a torrential river able to carry a large amount of sediment during seasonal flash-floods. Two macroplastic items were found at 68 and 255 cm below the core top (corresponding to the seafloor). Their association with terrestrial vegetal debris and their inclusion in decimetre-thick sandy/silty intervals showing coarsening- and fining-upward trends, suggest that they were deposited by hyperpycnal flows possibly triggered by flood events. These findings testify the potential of sedimentary flows in burying macroplastic at depth below the seafloor, especially in nearshore prodelta environments. Furthermore they raise the quest on the magnitude of macroplastic storage in the subsurface and on the lack of specific devices and strategies for their reckoning. Highlights: Macroplastic items retrieved within a sediment core collected in a prodelta deposit. Two items were found at 68 and 255 cm below the core top (i.e. the seafloor). Plastics were enclosed in sandy sediments and associated with vegetal debris. Plastics were transported and buried by river flood-generated hyperpycnal flows.